Gray Whale Calls Recorded near Barrow, Alaska, throughout the Winter of 2003–04 - Stafford, K.M.; Moore, S.E.; Spillane, M.; Wiggins, S. (ARCTIC, 2009)
Since the mid-1990s, gray whales (Eschrichtius robustus) have been reported with increasing frequency near Barrow, Alaska, during summer and autumn months. In collaboration with a broad-scale oceanographic study, three autonomous acoustic recorders were moored northeast of Barrow in October 2003 to provide capability for year-round detection of calls. Two recorders were recovered in September 2004, one from the continental slope (water depth = 316 m) and one from near the base of the slope (water depth = 1258 m). The shallow instrument recorded for roughly 3 months (87 days), and the deeper instrument for roughly 7.3 months (222 days). Gray whale calls were recorded on both instruments throughout their periods of operation. The calling rate at the shallower instrument was higher than at the deeper recorder, but surprisingly, the deeper instrument detected calls throughout the 2003–04 winter, though the calling rate diminished as winter progressed. Low-frequency N1/S1 pulses, the most common of the calls produced by gray whales, were recorded from deployment through December 2003 on the shallower of the two instruments and from deployment through May 2004 on the deeper instrument. Because this is the first-ever winterlong acoustic study, we cannot be certain that gray whales have not overwintered in the Beaufort Sea in the past. However, a combination of increasing population size and habitat alteration associated with sea ice reduction and warming in the Alaskan Arctic may be responsible for the extra-seasonal gray whale occurrence near Barrow. Depuis le milieu des années 1990, des baleines grises (Eschrichtius robustus) ont été signalées de plus en plus souvent près de Barrow, en Alaska, pendant les mois d’été et d’automne. En collaboration avec une étude océanographique à grande échelle, trois enregistreurs acoustiques autonomes ont été amarrés au nord-est de Barrow en octobre 2003 afin de pouvoir détecter les cris de baleine à l’année. Deux enregistreurs ont été récupérés en septembre 2004, un de la pente ...